Efektivitas Pendidikan dan Pelatihan dalam Meningkatkan Kompetensi Pegawai (Studi pada Diklat Kepemimpinan Tingkat IV Kota Malang Tahun 2014) - Diga Saffiar Ariandi (Jurnal Administrasi Publik, 2016)
Abstract: Effectiveness of Education and Training to Improving Employee Competency (Study on Leadership Training Level IV Malang 2014). Needs to be known that the effectiveness of education and training of the Civil Service is considered an important thing. Through the effectiveness of the education and training for employees, will be able to note the extent to which education and training can improve employee competence. The focus of this research is the effectiveness of education and training in improving the competence of employees as well as the Â supporting and inhibiting factors in the education and training of employees of the city of Malang. Based on the results of research, education and training that carried in the Malang city government is effectively able to improve the competence of employees, this can be known through some indicators of competencies that is the knowledge, skills, attitudes and behaviors, as well as increased employee motivation. Moreover as for supporting factor is the budget, existence of cooperation or partnership with the Training Agency of East Java Province. While inhibiting factors including Training Needs Analysis (AKD) were just been implemented in 2015, limited facilities and infrastructure, and there are a task that can not finished by the employees. Keywords: effectiveness, education and training, competency Abstrak: Efektivitas Pendidikan dan Pelatihan dalam Meningkatkan Kompetensi Pegawai (Studi pada Diklat Kepemimpinan Tingkat IV Kota Malang Tahun 2014). Perlu diketahui bahwa efektivitas dalam penyelenggaraan pendidikan dan pelatihan Pegawai Negeri Sipil dirasa merupakan suatu hal yang penting. Melalui efektivitas pendidikan dan pelatihan pegawai, nantinya dapat diketahuiÂ  sejauh mana pendidikan dan pelatihan dapat meningkatkan kompetensi pegawai. Fokus penelitian dalam penelitian ini yaitu efektivitas pendidikan dan pelatihan dalam meningkatkan kompetensi pegawai serta Faktor-faktor pendukung dan penghambat dalam pendidikan dan pelatihan pegawai Kota Malang. Berdasarkan hasil penelitian, pendidikan dan pelatihan yang dilaksanakan pemerintah Kota Malang secara efektif mampu meningkatkan kompetensi pegawai, hal ini dapat diketahui melalui beberapa indikator kompetensi yakni pengetahuan, keterampilan, sikap dan perilaku, serta motivasi pegawai yang meningkat. Selain itu adapun faktor pendukung yaitu anggaran, Adanya kerja sama atau kemitraan dengan Badan Diklat Provinsi Jawa Timur. Sedangkan penghambat diantaranya Analisis Kebutuhan Diklat (AKD) yang baru dilaksanakan tahun 2015, Terbatasnya sarana dan prasarana, Adanya beban tugas yang belum diseleseikan oleh pegawai. Kata Kunci: efektivitas, pendidikan dan pelatihan, kompetensi